Comparación de los elementos del costo de la producción del brócoli entre los productores del barrio San Vicente de la Parroquia Póalo - Jiménez Villalva, Enrique Israel (2019)
In the present investigation the elements of the cost were analyzed in the production of the broccoli to estimate the cost for kilo and for hectare of three producers of the neighborhood San Vicente. The bibliographical investigation was in use, as well as also the investigation of cross-country running of the capture of information to the small producers, for which managed the inductive method - deductively. Were analyzed and interpreted the results obtained of the application of the instruments as the interview and the direct observation, finally it was achieved to recreate a system of costs for processes for the production of the broccoli determining an investment of $ 539.33 for hectare and the cost for kilo was of $ 0,17 in the producer A, while the producer B had an investment of $ 537.62 and the cost for kilo was of $ 0.17, finally the producer C invested $ 507.08 and the cost for kilo was of $ 0.22. The results obtained of every producer change due to the fact that the producer C invests fewer inputs in each of the elements of the cost used inside the stages of the process of culture of the broccoli, which provokes that at the end of the production it does not obtain a qualit product. Whereas the price of sale for every producer on the different markets in average was of $ 0,27 cents, it is necessary to stress that this price is not fixed is taken as a referential sample of the behavior of the markets of (Latacunga, Pujilí and Saquisili) with it makes clear that it depends on an important factor since is the offer and the demand.